Cold water immersion recovery after simulated collision sport exercise - Pointon, M.; Duffield, R. (Medicine & Science in Sports & Exercise, 2012)
Purpose: This investigation examined the effects of cold water immersion (CWI) recovery after simulated collision sport exercise.